Viburnum Downy Mildew - Aaron J. Palmateer (EDIS, 2016)
Downy mildew on viburnum is currently a serious concern throughout Florida. Winters in south Florida combine high humidity with cool nights, creating ideal conditions for disease development. Downy mildews are caused by several different species that tend to be host specific. 3 is the pathogen that affects viburnum. This 5-page fact sheet describes the hosts, symptoms, and management practices for Viburnum Downy Mildew. Written by A. J. Palmateer and published by the Plant Pathology Department, June 2016.